THE SYNTHESIS OF MODIFIED EPOXY RESINS - Dr. Irade Abdullayeva Gurban; Elsevar Safarov Ziya; Guntaj Samadova Rahman (Scientific Research and Experimental Development, 2024)
Modern construction relies heavily on polymer compositions based on epoxy resins. Epoxy oligomers are widely used in the production of adhesives. Adhesive compositions mainly utilize epoxy resins branded as ED-8, ED-24, ED-24N, ED-20, ED-22, ED-16, and so on. Depending on their molecular weights, they can be liquid or solid. Some Japanese researchers have reported conducting studies on the synthesis of bio-based epoxy resins since the 1960s using wood biomass. Plant oils (such as soybean oil, linseed oil, and palm oil), tannins, rosins, bark, processed biomass, and lignin have been used as precursors in the synthesis of epoxy resin. The main advantage of these types of epoxy resins is their biological degradation capability. Among these bio-based epoxy resins, plant oil-based epoxy resins lead to weak heat resistance due to their non-aromatic chain structure, leading to the formation of mechanical and other performance characteristics, limiting their industrial applications. Therefore, in some industrial sectors, they were only used as plasticizers and modifying agents. For example, the addition of epoxidized soybean oil to petroleum-based bisphenol A epoxy with the isophorone-diamine system effectively reduces the maximum curing temperature and improves the water absorption and chemical resistance properties of the resulting epoxy resins [1-3]. Bio-based nanocomposites have been produced from bisphenol F diglycidyl ether (BFDGE) of montmorillonite clay, epoxidized linseed oil, and methyl tetrahydrophthalic anhydride. These new bio-based nanocomposites possess high elasticity modulus, glass transition temperature, and fracture toughness, making them potentially applicable in various industrial sectors. A new bio-based epoxy resin with double bond networks stabilized by itaconic anhydride has been prepared. Divinylbenzene and acrylate-epoxidized soybean oil were incorporated into the cured resin to enhance its final properties, demonstrating that its glass transition temperature, impact strength, flexural strength, and flexural modulus can be compared to conventional resin [3-7]. Dimer acid (the dimer of unsaturated C18 fatty acid) is another biologically derived material used in epoxy resin systems. Like plant oil-based epoxy resins, dimer acid-based epoxy resin also exhibits weak mechanical, dielectric, and thermal properties due to its non-aromatic structure and long side chains. As previously discussed, lignin is a naturally occurring polydisperse phenolic polymer. The presence of phenolic hydroxyl groups in lignin allows it to be used in the synthesis of various polymers, such as phenolic resins, epoxy resins, polyurethanes, and polyethers [7-11]. It is expected that lignin-based epoxy resins may possess similar properties to conventional petroleum-based epoxy resins. Lignin-based epoxy resins can be produced through three different methods [12,13].